ELISA technique standardisation for human toxocariasis diagnosis summary - Espinoza, Yrma (2003)
Objetive: To standardise ELISA technique for Toxocara canis human infection diagnosis by using excreted-secreted antigen prepared in our country. Material and methods: T. canis eggs were collected by incubation with formalin (2%) at 28oC in order to obtain third stage larvae that were freed and incubated in RPMI at 37°C for 7 days; the medium was replaced by a similar one and stored at - 20°C. Antigen was concentrated and protein dosage was made. Sera from patients with toxocariasis and newborns were used as positive and negative controls by ELISA technique, dilutions ¼ to 1/1024. Polystyrene plates were sensitised with antigen in several concentrations and conjugated peroxidase with horseradish IgG, anti human IgG and substrate OPD were used. Absorbance was read with spectrophotometer (Multiskan plus labsystems) at 492 nm. Cut off point was determined by negative sera absorbencies arithmetic mean plus 3 standard deviations. Results: Antigen concentration was 50 ug/mL, sera dilution 1/128, conjugate dilution 1/1000 with optical density above 0,241. Cconclusions: ELISA technique for serologic diagnosis of human infection by Toxocara canis could be used in epidemiological studies in our country. Its efficacy will be determined in future studies.